Analysis Of Legal Functions And Maqashid Sharia On Islamic Marriage Law In Indonesia - Maylissabet (Fakultas Syariah Univeritas Islam Madura, 2022)
This study discusses the analysis of the function of law and the analysis of Maqasid ash-Syariah on Islamic Marriage Law in Indonesia. The method used in this study, the author uses the type of normative research and conceptual approach. This type of normative research is a type of research that focuses on norms, rules, laws, and theoretical matters. The conceptual approach in question is as a theory to analyze the object of research. The questions that are the focus of this research are how to analyze the legal function of Islamic marriage law in Indonesia and how to analyze Maqasid Asy-Syariah on Islamic marriage law in Indonesia.